What is the optimal treatment in clinical stage T3N0M0 rectal cancer? - Tural, Deniz; Yıldız, Özcan; Elçin, Olgun; Erdamar, Sibel; Güney, Sabri; Demireli, Fuat; Büyükünal, Evin; Serdengeçti, Süheyla (Zerbinis Medical Publications, 2014)
Purpose: Some previous studies suggested that certain rectal cancer patients with stage T3N0 and favorable features may be adequately treated with surgery and adjuvant chemotherapy. However, the optimal management of clinical (c) T3N0 rectal adenocarcinoma based on preoperative imaging is unclear. In this study, we aimed to determine the frequency of lymph node metastases in patients clinically staged as T3N0 rectal adenocarcinoma following preoperative chemoradiotherapy (CTR). Methods: The medical records of 105 patients with clinico-imaging stage T3N0M0 rectal cancer who received preoperative CRT between 2004-2011 were retrospectively analyzed. Chemotherapy used concurrently with preoperative radiotherapy (RT) was protracted 5-fluorouracil (5FU) infusion. Results: Twenty-seven percent of the patients clinically staged as T3N0 before preoperative CRT had pathological (p) lymph node involvement on surgical material. The rate of pathological lymph node involvement was 0% in pT1, 20% in pT2, 35% in pT3 and 34% in pT4 patients. A significant association was demonstrated between pT stages and pN status (p=-0.03). Conclusion: Our study demonstrated that the accuracy of preoperative imaging for staging rectal cancer is limited because at least 27% of the patients may have undetected lymph node involvement after preoperative CRT in surgical material.
WOS: 000334153000014
PubMed ID: 24659649
Keywords: Clinical T3; N0 Rectal Adenocarcinoma; Preoperative Imaging; Understaged